2003
DOI: 10.1046/j.1439-0396.2003.00429.x
|View full text |Cite
|
Sign up to set email alerts
|

Studies on feed digestibilities in captive Asian elephants (Elephas maximus)

Abstract: SummaryIn order to test the suitability of the horse as a nutritional model for elephants, digestibility studies were performed with six captive Asian elephants on six different dietary regimes, using the double marker method with acid detergent lignin as an internal and chromium oxide as an external digestibility marker. Elephants resembled horses in the way dietary supplements and dietary crude fibre content influenced digestibility, in calcium absorption parameters and in faecal volatile fatty acid composit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
81
4

Year Published

2005
2005
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(99 citation statements)
references
References 21 publications
14
81
4
Order By: Relevance
“…Caanitz et al (1991) also observed no effect of exercise on feed intake in horses. The DMI observed in present study was higher than that recorded by Clauss et al (2003) in adult Asian elephants fed hay-based diets. In this experiment, sugarcane was the primary ingredient which is relished by elephants (Lihong et al 2007).…”
Section: Feed Consumption Nutrient Intake and Apparent Digestibilitycontrasting
confidence: 80%
“…Caanitz et al (1991) also observed no effect of exercise on feed intake in horses. The DMI observed in present study was higher than that recorded by Clauss et al (2003) in adult Asian elephants fed hay-based diets. In this experiment, sugarcane was the primary ingredient which is relished by elephants (Lihong et al 2007).…”
Section: Feed Consumption Nutrient Intake and Apparent Digestibilitycontrasting
confidence: 80%
“…The few reports available indicate that elephants resemble the equine species with reference to calcium status 4,20,41 as elephants absorb calcium almost unlimitedly from the intestines similar to the horse and in contrast to the bovine species. 8,32 On the other hand, high urinary calcium concentrations have also been reported in captive elephants 29 similar to the equine species.…”
Section: Discussionmentioning
confidence: 95%
“…The absolute value is derived from the calculation based on digestibility trials with domestic horses. While the digestive efficiency of horses is similar to some other large hindgut fermenters, such as the white rhinoceroses (Ceratotherium simum) (Kiefer, 2002) and Indian rhinoceroses (Rhinoceros unicornis) (Clauss et al, 2005a), it was demonstrated that the horse is not an adequate model for digestion in elephants (Clauss et al, 2003) or black rhinoceroses (Diceros bicornis) . As browsers, tapirs could be expected to actually achieve lower digestion coefficients on comparable diets than horses.…”
Section: Discussionmentioning
confidence: 99%